Co‐condensation synthesis of well‐defined mesoporous silica nanoparticles: effect of surface chemical modification on plasmid DNA condensation and transfection. Issue 8 (18th September 2017) - Mahmoodi, Mahdokht; Behzad‐Behbahani, Abbas; Sharifzadeh, Sadigheh; Abolmaali, Samira Sadat; Tamaddon, AliMohammad
Abstract : Chemically modified mesoporous silica nanoparticles (MSNs) are of interest due to their chemical and thermal stability with adjustable morphology and porosity; therefore, it was aimed to develop and compare the MCM‐41 MSNs functionalised with imidazole groups (MCM‐41‐Im) to unmodified (MCM‐41‐OH) and primary amine functionalised (MCM‐41‐NH2 ) MSNs for experimental gene delivery. The results show efficient transfection of the complexes of the plasmid and either MCM‐41‐NH2 or MCM‐41‐Im. Furthermore, following transfection of HeLa cells using MCM‐41‐Im, an enhanced GFP expression was achieved consistent with the noticeable DNase1 protection and endosomal escape properties of MCM‐41‐Im using carboxyfluorescein tracer.